Lubrication Systems: Tribo‐Induced Structural Transformation and Lubricant Dissociation at Amorphous Carbon–Alpha Olefin Interface (Adv. Theory Simul. 2/2019). Issue 2 (4th February 2019) - Li, Xiaowei; Wang, Aiying; Lee, Kwang‐Ryeol
Abstract : In article number1800157, Xiaowei Li, Aiying Wang, and Kwang‐Ryeol Lee report that introducing alpha olefins (AOs) into an a‐C/a‐C sliding interface lowers friction. A transformation of interfacial structure and the dissociation of AOs is revealed. In consequence, the friction mechanism differs with the type of AO. Disclosing the scission sites of the AOs provides a guide for designing improved lubricants.